Students’ Knowledge of Mental Health Literacy as a Prevention of Mental Health Problems - Rubaatin, Al Fiati; Adinugraha, Hendri Hermawan; Shulthoni, M. (Cognitionis Civitatis et Politicae, 2024)
This study identifies and analyzes students' understanding of mental health literacy for overcoming mental health problems that occur to them. A descriptive-qualitative method was used to systematically review the data. This study shows that the majority of students at UIN Pekalongan have an understanding of mental health and mental health literacy and how it affects them. However, there are still some students who have not fully implemented mental health literacy, which results in the absence of the influence of mental health literacy on them. Mental health literacy can affect a person's mental health if they truly understand and apply it in their daily lives, such as managing their stress. Stable mental health is when a person can deal with the pressures of normal life, work productively, and contribute to their community. Conversely, people who do not understand mental health will find it difficult to overcome mental health problems. There needs to be media assistance that can help students understand health literacy, one of which is social media. However, social media can also interfere with mental health, so information obtained must still be considered to avoid unwanted impacts. It is hoped that everyone can improve mental health literacy, one of which is students. Because mental health literacy is useful for oneself as well as others, each individual can learn how to respond to friends or family who experience mental problems in an appropriate way.